KINERJA LULUSAN SMK KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN DI INDUSTRI OTOMOTIF SURABAYA - Arizal, Heru (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
The purpose of this study is to find out the performance of graduates of Vocational High School competency expertise in engineering light vehicle that has been worked  in the automotive industry, also analyzed the relationship of school accreditation, UKK value and duration of working with performance. The research was held in April 2014 in Surabaya City with the sample in the automotive industry sole agent were 43 graduates of non automotive industry sole agent as much as 59 graduates and use descriptive research as well as quantitative tracer studies. The process of data retrieval  using a questionnaire which has been validated by an experts and scholars have conducted trials to determine the reliability of the instrument and the data were analyzed using multiple regression analyses with normal qualify, linearity, multicollinearity and heteroscedasticity. The results showed satisfactory the performance of vocational graduates. Based on the industry's in graduate work at the automotive industry sole agent better than non automotive industry sole agent. Accreditation of schools does not have a relationship with the performance, because the company accreditation is only use during the initial selection or administration, where the origin graduates accounted for only 10% of a person's success and 90% coming from the rest the quality of individual. UKK score and duration of  work has a significant relationship with performance and Vocational High School graduates, as well as all independent variables together research related to performance. UKK score associated with the performance and capabilities due to an embodiment of the base that is owned by someone, if  its basic capabilities is the ability to both receive and manage information / knowledge would also be good. The duration of work is more dominant due to factors related to the performance of repetitive activities so without realizing that they have received a learning process and settle in their mindset. Keywords: Performance, Accreditation, UKK, the Old Works.